Comparative proximate analysis and calcium composition between admiral yoghurt and local (Fulani) yoghurt sold at Mayo-Belwa town, Adamawa state, Nigeria / Mubarak Muhammad Dahiru, Muhammed Bobbo Hamid and Neksumi Musa - Dahiru, Mubarak Muhammad; Hamid, Muhammed Bobbo; Musa, Neksumi (UiTM Press, 2022)
The varying in cow breeds for milk sources in yoghurt production could provide a difference in yoghurt quality, an important factor to be evaluated. The study aimed to compare the proximate and calcium composition of Admiral yoghurt and Local (Fulani) yoghurts which, the milk source, is from imported and indigenous breeds, respectively. The proximate and calcium compositions of Admiral yoghurt and Fulani yoghurts from three districts (Mbilla, Binkola, Mayo farang) sold in Mayo-belwa local government Area of Adamawa State, Nigeria, were determined. The result of the proximate composition indicated a significant difference (p < 0.05) between all the proximate Admiral yoghurt and the Fulani yoghurts except moisture. Admiral yoghurt had more crude fat (6.97%) than the Fulani yoghurts (4.98-4.66 %). However, the Fulani yoghurts had more ash (0.73-0.68 %), crude protein (4.88-3.81 %), crude fibre (0.04-0.03 %) and carbohydrate (3.69-3.48 %). The result also showed that all the Fulani yoghurts contain more calcium (3.88-3.46 mg/ml) than Admiral yoghurt (2.65 mg/ml). The overall result revealed that the Fulani yoghurts had a comparable proximate and calcium composition with Admiral yoghurt based on their proximate and calcium composition.